2022
DOI: 10.3390/app12042055
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Vocal Tract and Glottal Source Spectral Cues in the Generation of Acted Happy and Aggressive Spanish Vowels

Abstract: The source-filter model is one of the main techniques applied to speech analysis and synthesis. Recent advances in voice production by means of three-dimensional (3D) source-filter models have overcome several limitations of classic one-dimensional techniques. Despite the development of preliminary attempts to improve the expressiveness of 3D-generated voices, they are still far from achieving realistic results. Towards this goal, this work analyses the contribution of both the the vocal tract (VT) and the glo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Regarding the addition of expressiveness to the numerical generation of voice, previous works have been developed using ST-QCP to analyse the characteristics of GS and VT in aggressive and happy female vowels [9,14]. However, the results obtained in the present study suggest that maybe it would be better to use QCP without the spectral tilt correction when dealing with female speech.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Regarding the addition of expressiveness to the numerical generation of voice, previous works have been developed using ST-QCP to analyse the characteristics of GS and VT in aggressive and happy female vowels [9,14]. However, the results obtained in the present study suggest that maybe it would be better to use QCP without the spectral tilt correction when dealing with female speech.…”
Section: Discussionmentioning
confidence: 71%
“…Additionally, the manipulation of the vocal tract characteristics using simulations based on finite element methods (FEM) has enabled the production of effects such as the singing formant in 3D-based articulatory voice generation [12]. Therefore, from these works, it can be concluded that, for the production of expressive speech, a proper model and adjustment of the vocal tract response and the glottal source signal is of paramount importance, as is considering their varying relevance depending on the target speaking style [13,14].…”
Section: Introductionmentioning
confidence: 99%